DEVELOPMENT OF CRITICAL THINKING ABILITY ORIENTED TEXTBOOK ON ELECTROLYTE AND NON-ELECTROLYTE SOLUTION MATERIALS - Saputri, Silpia Vilda; Dayanti, Nelly; Sari, Ratna Kumala; Sartika, Rody Putra; Hadi, Lukman (Jurnal Pendidikan Matematika dan IPA, 2022)
This study aims to produce electrolyte and non-electrolyte textbooks oriented to critical thinking skills through a problem based learning model that will measure the level of feasibility, response to students and their level of effectiveness. This research refers to the research and development model recommended by Borg Gal. Data on feasibility rate and response of students are obtained in the form of quantitative data which is converted by the percentage scale of product quality according to the Likert scale. The effectiveness of the book is measured using the average value of N-Gain. The conclusions of this study are textbooks for electrolyte and non-electrolyte solutions with feasibility rate of 95.11% criteria "very high", the response rate of students in the early field test 86.92% and the main field test 87.11% in "very high" category, level book effectiveness with the N-Gain average of 0.62 in "medium" category.